The start of systems biology in Ukraine - Obolenskaya, M.Yu.; Tokovenko, B.T.; Kuklin, A.V.; Frolova, A.A.; Rodriguez, R.R.; Dotsenko, V.A.; Dragushchenko, O.O. (Вiopolymers and Cell, 2014)
The first laboratory of Systems Biology in Ukraine (IMBIG NASU) represents a track record of its scientific results. They include the pioneered development of a web-based tool for genome-wide surveys of eukaryotic promoters for the presence of transcription factors binding sites (COTRASIF); the deciphered mechanisms of the fine-tuned and balanced response of primary hepatocytes to interferon alpha levels recorded after partial hepatectomy; the elaboration of a novel method of gene regulatory network inference compatible with GRID environment and the development of a stoichiometric model of folate-related one carbon unit metabolism in human placenta and its application for the characteristics of the system’s behavior as a whole at different human pathologies.